Impact of Pharmacists’ Intervention in Breastfeeding Mothers’ Knowledge about Child Immunization - George, Gifty Acsa; Kandur, Manjunath; Idicula, Milju Kanniyamannil; Sasikumar, Salini Kizhakkepayipottu; Ramachandran, Arun Chandran (Journal of Pharmacy Practice and Community Medicine)
Vaccines are recommended during the early phases of life to prevent against the serious deadly diseases that may occur in the long run. Aim: The aim of the study is to find out the impact of Pharmacists’ intervention on Knowledge about Immunization among breast feeding mothers. The study also aimed at assessing the attitude and practice of mothers regarding breastfeeding and immunization, identifying the barriers in effective immunization. Materials And Methods: An educational interventional study was carried out among 192 samples in selected villages of Bengaluru. The data was collected by using self-designed content validated questionnaire and responses were recorded. All information’s were processed and analyzed by using Microsoft excel and latest version SPSS software. Results: It was found that most of the mothers’ knowledge (pre-test average score was 6.16 and post-test average score was 10.19) towards child immunization was found to be improved after suitable intervention. Time, cost, continuous relocation of residence and distance were identified as barriers in effective immunization. Conclusion: Immunization is an effective way of reducing child morbidity and mortality. According to our study, most of the mothers agreed to the benefits of immunization. The major hindrances of child immunization were also identified. With the right information and guidance provided by means of educational programs or by providing facilities for door-to-door immunization services we can further enhance mothers’ knowledge, attitude and practice regarding immunization and breastfeeding.
Keywords: Immunization; Breastfeeding Mothers; Barriers; Adverse Event Following Immunization; Morbidity; Mortality; Intervention